2020
DOI: 10.1002/hep.31031
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐22 Ameliorates Neutrophil‐Driven Nonalcoholic Steatohepatitis Through Multiple Targets

Abstract: Background and Aims Nonalcoholic fatty liver disease encompasses a spectrum of diseases ranging from simple steatosis to nonalcoholic steatohepatitis (NASH), cirrhosis, and liver cancer. At present, how simple steatosis progresses to NASH remains obscure and effective pharmacological therapies are lacking. Hepatic expression of C‐X‐C motif chemokine ligand 1 (CXCL1), a key chemokine for neutrophil infiltration (a hallmark of NASH), is highly elevated in NASH patients but not in fatty livers in obese individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 38 publications
5
124
0
1
Order By: Relevance
“…However, mice fed a HFD only showed weak p38α activation, which upregulated genes involved in fatty acid β-oxidation that may act to compensate for hepatocyte fat accumulation. 26,27 In patients with NASH, serum NET levels are markedly increased. In an animal model of NASH, free fatty acids also stimulated the formation of NETs in vivo and in vitro.…”
Section: The Role Of Neutrophils In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…However, mice fed a HFD only showed weak p38α activation, which upregulated genes involved in fatty acid β-oxidation that may act to compensate for hepatocyte fat accumulation. 26,27 In patients with NASH, serum NET levels are markedly increased. In an animal model of NASH, free fatty acids also stimulated the formation of NETs in vivo and in vitro.…”
Section: The Role Of Neutrophils In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Although progress has been made in the potential mechanisms of NAFLD and in the identification and development of new therapeutic targets, many problems remain to be resolved and there are no approved therapeutic drugs [28]. IL-22 plays a particular role in alleviating the progression of NAFLD [29].…”
Section: Nonalcoholic Fatty Liver Injurymentioning
confidence: 99%
“…Adenovirus-mediated overexpression of Cxcl1 significantly elevated neutrophil infiltration in the liver of mice fed an HFD for 3 months. 50 Increased neutrophil population promoted ROS production which led to an activation of apoptosis signal-regulating kinase 1 (ASK1) and p38 mitogen-activated protein kinase (MAPK), thereby activating the signaling pathways leading to apoptosis-and ER stress-induced hepatocyte death. 51 DNA damage, oxidative stress, and other intrinsic apoptotic stimuli incurred by infiltrated neutrophils activate the mitochondrial apoptotic pathway of hepatocytes.…”
Section: Overexpression Of Cxcl1 Promotes Ste-atosis-to-nash Progressionmentioning
confidence: 99%
“…ROS production can also disturb the protein folding process within the ER lumen by changing the redox status, which further cause ER stress. 52,53 It has been also demonstrated that infiltrated neutrophils cause hepatocyte death through p47 phox -dependent oxidative burst and subsequent activation of ROS-sensitive stress kinases such as p38 MAPK and JNK, 50 which in turn facilitates inflammatory and fibrogenic processes and exacerbates steatosis-to-NASH progression. Microarray analysis revealed that HFD/CXCL1-induced NASH possessed expression profiles of inflammatory and fibrogenic genes, which are similar to those of NASH patients, supporting the notion that Cxcl1 overexpression results in steatosis-to-NASH progression in HFD-fed mice.…”
Section: Overexpression Of Cxcl1 Promotes Ste-atosis-to-nash Progressionmentioning
confidence: 99%
See 1 more Smart Citation